Efeitos da Aplicação da Metodologia Lean Thinking no Pronto Atendimento de um Hospital Geral - Maysa de Paula Pacheco Batista (2021)
Health services in Brazil have inefficiencies regarding the care provided to patients and their caregivers. It is common to have long waiting lines, excessive bureaucracy, and little organization of processes and insufficient information, which makes the customer have a perception of the low quality of the provided service. The Lean Thinking methodology originated in the manufacturing industry was introduced to the healthcare segment and is currently used as a way to reduce these inefficiencies. Its principles in health are aimed at improving the quality of care and customer service and the objective is to eliminate waste and ensure greater attention in providing care, through the continuous system improvement. It is assumed that the use of this methodology inside the hospital influences the customers’ perception regarding the provided service and a consequent improvement in satisfaction rates. This research objective was to analyze the implications of the Lean Thinking methodology on the quality of services provided in the emergency room of a general hospital and on customer satisfaction. The study was carried out in a large general hospital in Belo Horizonte – Minas Gerais and we used a case study, with a qualitative approach and descriptive character. The data collection technique included documents and semi-structured interviews with the leaders from the analyzed unit. Qualitative data were evaluated using the content analysis technique. It was evident in our results that the Lean Thinking methodology had the following effects: reduced waiting time for medical care, greater care fluidity and specialization of the clinical staff regarding the cases’ types. It also allowed the care of different profiles of patients with agility and security, and improved the experience and satisfaction of the served customer. We concluded that the experience of implementing the Lean Thinking methodology, in the emergency room of a general hospital, brought quality and safety gains for the care provision and implied an improvement in customer satisfaction. Finally, we developed a technical report with practical guidelines for healthcare organizations that wish to implement the Lean Thinking methodology.